Vaginal epithelioid angiosarcoma. Issue 12 (December 1998) - McAdam, J A; Stewart, F; Reid, R
Abstract : A case of epithelioid angiosarcoma of the vagina is described. Only five cases of angiosarcoma at this site have been reported, three of which followed radiotherapy for other gynaecological malignancies. None is described as an epithelioid angiosarcoma, an unusual and recently described variant which is readily confused with carcinoma. This is thought to be the first reported epithelioid angiosarcoma at this site and highlights the difficulties in diagnosis.